Dysregulation of Striatal Dopamine Receptor Binding in Suicide - Fitzgerald, Megan L; Kassir, Suham A; Underwood, Mark D; Bakalian, Mihran J; Mann, J John; Arango, Victoria (Neuropsychopharmacology (New York, N.Y.), 2017)
Inconsistent evidence implicates disruptions of striatal dopaminergic indices in suicide and major depression. To determine whether there are alterations in the striatal dopamine system in suicide, we conducted a quantitative autoradiographic survey of dopamine transporter (DAT; [ H]mazindol), D1 receptor ([ H]SCH23390), and D2 receptor ([ H]sulpiride) binding in the dorsal striatum postmortem from matched suicides and controls. Axis I and axis II psychiatric diagnosis, recent treatment history, and early life adversity (ELA) were determined by psychological autopsy. Mean DAT, D2, and D1 receptor binding did not differ in suicide. However, there was a positive correlation between D1 and D2 receptor binding in the dorsal striatum of control subjects (R =0.31, p<0.05) that was not present in suicides (R =0.00, p=0.97). In suicides and controls with reported ELA, there was no correlation between striatal DAT and D1 receptor binding (R =0.07, p=0.33), although DAT and D1 receptor binding was positively correlated in subjects with no report of ELA (R =0.32, p<0.05). After controlling for age, there were no significant ELA-related mean differences. Binding of D1 receptors and DAT throughout the striatum correlated negatively with age (D1 receptor: R =0.12, p<0.05; DAT: R =0.36, p<0.001). There appears to be an imbalance in dopaminergic receptor and transporter expression related to suicide that differs from that associated with ELA or age.